Sport Psychology in Sports, Exercise and Physical Activity - Nielsen, Hilde G. (IntechOpen, 2021)
Sports psychology is an interdisciplinary science for the purpose of increased participation in sports and physical activity to improve health and wellbeing. It addresses everything from optimal performance and wellbeing of athletes to developing mental and social aspects of participation to systemic issues associated with sports settings and organizations. This book introduces readers to topics within sports psychology with a special focus on motivation, behavior change, and personalities.